Refugee-Background Students in Canadian French Immersion Programs: Exploring the Perspectives and Ideologies of Educators - Davis, Stephen (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2024)
French immersion (FI) programs are becoming increasingly culturally and linguistically diverse as a result of growing migration to Canada. In the present mixed-methods study, I explore the perspectives and ideologies of teachers, principals, and central office staff in eight school divisions in Saskatchewan, Manitoba, and Alberta with respect to refugee-background students in FI programs. Through the triangulation of survey responses (N=126) and interviews (N=40), I examine perspectives pertaining to four themes: 1) suitability of FI for refugee-background students; 2) language learning; 3) challenges facing refugee-background students; and 4) supports and resources in FI programs. Adopting the theoretical perspective of sociolinguistics for change, I discuss three underlying ideologies shaping the perspectives of FI educators across the Canadian Prairies: 1) English-first ideologies; 2) deficit ideologies; and 3) ideological tensions between inclusion and support.